Acute Aerobic Swimming Exercise Induces Distinct Effects in the Contractile Reactivity of Rat Ileum to KCl and Carbachol - Araujo, Layanne C. da Cunha; Souza, Iara L. L. de; Vasconcelos, Luiz H. C.; Brito, Aline de Freitas; Queiroga, Fernando R.; Silva, Alexandre S.; Silva, Patrícia M. da; Cavalcante, Fabiana de Andrade; da Silva, Bagnólia A. (Frontiers in Physiology, 2016)
Aerobic exercise promotes short-term physiological changes in the intestinal smooth muscle associated to the ischemia-reperfusion process; however, few studies have demonstrated its effect on the intestinal contractile function. Thus, this work describes our observations regarding the influence of acute aerobic swimming exercise in the contractile reactivity, oxidative stress and morphology of rat ileum. Wistar rats were divided into sedentary (SED) and acutely exercised (EX-AC) groups. Animals were acclimated by 10, 10 and 30 min of swimming exercise in intercalated days one week before exercise. Then they were submitted to forced swimming for 1 h with a metal of 3% of their body weight attached to their body. Animals were euthanized immediately after the exercise section and the ileum was suspended in organ baths for monitoring isotonic contractions. The analysis of lipid peroxidation was performed in order to determinate the malondialdehyde (MDA) levels as a marker of oxidative stress, and intestinal smooth muscle morphology by histological staining. Cumulative concentration-response curves to KCl were altered in the EX-AC with an increase in both its efficacy and potency (Emax = 153.2 ± 2.8%, EC50 = 1.3 ± 0.1 x 10-2 M) compared to the SED group (Emax = 100%, EC50 = 1.8 ± 0.1 x 10-2 M). Interestingly, carbachol had its efficacy and potency reduced in the EX-AC (Emax = 67.1 ± 1.4%, EC50 = 9.8 ± 1.4 x 10-7 M) compared to the SED group (Emax = 100%, EC50 = 2.0 ± 0.2 x 10-7 M). The exercise did not alter the MDA levels in the ileum (5.4 ± 0.6 µmol/mL) in the EX-AC compared to the SED group (8.4 ± 1.7 µmol/mL). Moreover, neither the circular nor the longitudinal smooth muscle layers thickness were modified by the exercise (66.2 ± 6.0 and 40.2 ± 2.6 µm, respectively) compared to the SED group (61.6 ± 6.4 and 34.8 ± 3.7 µm, respectively). Therefore, the ileum sensitivity to contractile agents is differentially altered by the acute aerobic swimming exercise, without affecting the oxidative stress and the morphology of ileum smooth muscle.